NEED ANALYSIS OF ENGLISH LANGUAGE SKILL FOR HOTEL FRONT OFFICE STAFF IN THE MOUNT BROMO TOURISM AREA - Kamarang, Apliandi; Zainuddin; Lestari, Wahyu (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the English language needs required by front office hotel staff in the tourist area of Mount Bromo, Probolinggo. The background of this research lies in the importance of English communication competence for hospitality workers in serving international tourists, particularly in major tourist destinations such as Bromo. A descriptive qualitative approach was employed, with data collected through in-depth interviews, field observations, and questionnaires administered to hotel staff and front office managers. The findings indicate that the primary language needs include skills in greeting, reservation handling, check-in/out procedures, giving directions, and handling complaints within the context of hotel services. Furthermore, it was found that most staff has not received structured English training nor accessed context-relevant learning materials. These findings highlight the need for developing English training programs based on real workplace situations and integrating ESP (English for Specific Purposes) content into tourism training in the Probolinggo region. The results of this study can directly inform the development of targeted English training modules, support policy initiatives for workforce upskilling in the tourism sector, and guide the integration of ESP-based content into vocational curricula for hospitality education.